Changes in the aerobic vaginal flora after treatment with different intravaginal devices in ewes - Manes, Jorgelina (2010)
The objective of this study was to characterize the vaginal bacterial flora and subsequent pregnancy rates after AI in sheep subjected to 4 different estrous synchronization regimes – the use of two intravaginal devices (silicone or polyurethane sponges), and two different treatment periods (7 or 14 days). Twenty-one multiparous Texel ewes were randomly allocated to 4 treatment groups during the breeding season. In the ewes from Group I (n = 6) and Group II (n = 5), a polyurethane sponge containing 60 mg MAP was inserted in the vagina for a period of 7 or 14 days, respectively. In the ewes of Group III (n = 5) and Group IV (n = 5), an intravaginal progesterone releasing insert (IVP4) containing 160 mg of progesterone in an inert silicone device, was inserted for 7 or 14 days, respectively. At device withdrawal, each ewe was treated with 200 IU eCG i.m. Standard bacteriological procedures were performed on vaginal mucus samples obtained before the introduction of the devices, at device withdrawal and on the day of AI in all groups. Estrus was recorded with the aid of vasectomized rams every 12 h, and AI was performed 52–54 h after device withdrawal, using fresh semen. The intervals between device withdrawal and estrus were: Group I: 56.4 ± 21.5 h; Group II: 42.0 ± 33.9 h; Group III: 51.6 ± 21.5 h; Group IV: 37.2 ± 10.7 h, while the pregnancy rates were: Group I: 83.3%; Group II: 60.0%; Group III: 60.0%; Group IV: 60.0%. The pregnancy rates and the interval between device withdrawal and the occurrence of estrus did not differ between treatments. The predominant bacterial flora population at device insertion was mostly gram positive (G+) (90%) bacteria. The strains most frequently found were Bacilllus sp., Staphylococcus sp. and Corynebacterium sp. Of the 19 isolates made at device removal, 79% were gram negative, with the Escherichia sp. being the most frequently isolated. At the time of AI and regardless of the device used, the 14-day treatment group presented an initial gram positive bacterial flora, while the 7-day groups presented gram negative flora (82%). It could be concluded that the use of intravaginal devices, regardless of their composition (silicone or polyurethane), may generate changes in the normal vaginal bacterial flora of the vaginal mucus. These changes did not reflect on the subsequent fertility. The use of intravaginal devices should however include the adoption of strict hygiene procedures, to minimize the growth of bacterial flora.